2012
DOI: 10.1017/s0142716412000598
|View full text |Cite
|
Sign up to set email alerts
|

Noun case suffix use by children with specific language impairment: An examination of Finnish

Abstract: Finnish-speaking children with specific language impairment (SLI, N = 15, M age = 5;2), a group of same-age typically developing peers (TD-A, N = 15, M age = 5;2) and a group of younger typically developing children (TD-Y, N = 15, M age = 3;8) were compared in their use of accusative, partitive, and genitive case noun suffixes. The children with SLI were less accurate than both groups of TD children in case marking, suggesting that their difficulties with agreement extend to grammatical case. However, these ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Children with SLI made inflection errors, but surprisingly to quite a small extent. However, previous research has shown that grammatical difficulties are evident in verb and noun inflections in Finnish children with SLI when examined by specific probe tasks (Kunnari et al, 2011;Leonard et al, 2012). In this study, the stories of children with SLI were short.…”
Section: Discussionmentioning
confidence: 61%
“…Children with SLI made inflection errors, but surprisingly to quite a small extent. However, previous research has shown that grammatical difficulties are evident in verb and noun inflections in Finnish children with SLI when examined by specific probe tasks (Kunnari et al, 2011;Leonard et al, 2012). In this study, the stories of children with SLI were short.…”
Section: Discussionmentioning
confidence: 61%
“…It is interesting to note that accusative case is relatively difficult for children with DLD acquiring Finnish, another agglutinating language (Leonard et al . 2014). As in Turkish, the appearance or absence of this suffix in Finnish depends on the context.…”
Section: Discussionmentioning
confidence: 99%
“…One factor that emerges from these studies is these children's difficulty mastering the morphophonological changes that are often required when a suffix must be added to the stem (Leonard et al . 2014). In language such as Finnish and Hungarian, these changes are relatively complex.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Finnish, children with DLD often use the nominative case (the most frequently occurring case in the language) in place of the genitive, partitive and accusative cases (Leonard et al . ). Case difficulties can also be seen in Japanese (Murao et al .…”
Section: Factor 2: Case Confusionmentioning
confidence: 97%